Deployment of next-generation sequencing approach for variant detection in myocardial infarction: A concise investigation - Desaraju Suresh Bhargav; Nadeem Siddiqui; Bhadra Murthy V; Vijaya Tartte; Vanaja V (Journal of Krishna Institute of Medical Sciences University)
Background: A fatal health issue termed Myocardial Infarction (MI) is characterized by an acute loss of oxygen and blood supply to the heart muscles, ultimately leading to necrosis. This can turn life threatening if left untreated and undiagnosed at early stages. Elevated plasma LDL cholesterol involved in plaque formation and thinning of arterial walls is believed to the main culprit. Till date there are no preventive diagnosis/screening molecular mechanism to identify the responsible markers for this cholesterol metabolism and associated risk factors. Aim and Objectives: To identify the predominantly expressed genes associated with MI. The purpose of this work was to aid in the identification of biomarkers for the genetic diagnosis of MI leading to better understanding of the relation between genes involved in coronary heart diseases and their molecular mechanism. Material and Methods: This was a case control study in which patients attending the Cardiology Department of Sri Venkateswara Institute of Medical Sciences (SVIMS) recruited and initially evaluated with all biochemical parameters. After taking written informed consent, DNA samples were collected and subjected to NGS sequencing studies; a 17-gene customized MI panel was designed for targeted sequencing. The obtained data was analysed and identified variations within the selected genes were given priority for further investigation. Results: Variants in the APOB, MTHFR, WDR12, CELSR2, and MIA3 genes were identified as more predominant in the sequenced individuals and two novel variants were observed from CELSR2 which were not reported previously. Conclusion: To ascertain pathogenicity and role in the emergence of MI-related disorders these genes were mapped to online databases. Interestingly we found majority of genes from designed MI panel exhibit a variable effect upon the probability to acquire CAD as well as the severity towards variety of coronary heart diseases.